Transformasi Karakter Qurani: Tinjauan Materi Dakwah - Arifin, Zaenal (INSTITUT PEMBINA ROHANI ISLAM JAKARTA, 2024)
This study discusses the formation of Qur'anic character through Islamic preaching and its relationship with the character education values set by the government. The Qur'an teaches that ethics towards Allah and the Prophet are the main foundation for building noble character, which is then reflected in human relationships. Through Qur'anic-based preaching, values such as religiosity, honesty, tolerance, discipline, and responsibility can be applied in everyday life. Using a qualitative approach with descriptive analysis, this study examines preaching materials, including Qur'anic texts and preaching delivered through lectures, books, and digital platforms. The findings indicate that Islamic preaching not only focuses on spiritual character formation but also strengthens moral values that support character development in all aspects of life, including curiosity, creativity, environmental awareness, and national spirit.